Study of a hot asphalt mixture response based on energy concepts (2011)
The main objective of the research reported in this paper is to determine the response of a hot mix asphalt (HMA) in terms of both the tensile strength and energy parameters (based on the assessment of the force-displacement curve) as potential tools for improving the HMA mixture design. The HMAs analyzed were fabricated using a 60-70 penetration asphalt binder, dense-graded aggregate, mineral filler, and different types and contents of mineral filler replacements (i.e., lime, cement, and fly ash). The indirect tensile test was conducted to determine both the HMA tensile strength and force-displacement curve, which allowed for the computation of the HMA toughness as well as the energies involved in the process before and after reaching the tensile strength. Corresponding results suggest that the replacement of mineral filler by cement, lime, and fly ash modified the HMA response in terms of both the tensile strength and energy parameters. In addition, analysis of the energy parameters discussed proved to be useful for determining the optimum mineral filler content of HMA. Consequently, analysis of these energy parameters can benefit the HMA mixture design process.